A simple fabrication of Mn doped SnO2 nano particles towards improved congored degradation photocatalytic activity. (2023) - Rajeswaran, P.; Shanmuganathan, M.; Shanmuga sundari, T.; Elavarasan, A.; Sivakarthik, P.
Abstract: Transition metal doped semiconductor metal oxide nanostructured materials has drawn serious attention due to their remarkable photo catalytic activity. In this work, we used a simple chemical method to synthesize pristine as well as Mn-doped SnO2 nanoparticles. Powder X-ray diffraction results reveal that both pristine and Mn-doped SnO2 nanoparticles are translucent with a tetragonal phase with highly crystallinity. TEM analysis reveals the spherical morphology with agglomeration (TEM).UV–Vis DRS signify that reduction of band gap energy with the increase of Mn concentration levels(0, 2, 6%wt). The structural properties of a material are ascertained using the Fourier transform infrared spectroscopy technique. The photo catalytic performance of as synthesized materials was investigated towards the degradation of Congo red in an aqueous solution under visible light irradiation. The photo catalytic efficiency of Mn (6 wt%) doped with SnO2 has a significantly greater Mn content than the pristine SnO2 . The mechanism for enhanced photo catalytic activity of SnO2 discussed in detail.